Aerogel incorporated flexible nonwoven fabric for thermal protective clothing. (October 2021) - Shaid, Abu; Bhuiyan, M.A. Rahman; Wang, Lijing
Abstract: Aerogel-nonwoven fabrics are gradually emerging as a promising alternative in the field of thermal protective textiles. Although currently available commercial aerogel-nonwovens can provide some degree of flexibility and find their way into the conventional textiles, their flexibility has not yet reached an acceptable level essential for clothing comfort. Fabric flexibility is important for the aesthetics, comfort, and functionality of clothing. This article demonstrates the design and fabrication of an aerogel-nonwoven fabric as a thermal liner in a multilayered protective clothing system that is significantly more flexible than commercial aerogel-nonwoven fabrics. The developed aerogel-nonwoven composite possesses almost similar dry and radiant heat resistance but inferior contact heat resistance in comparison to commercial aerogel nonwovens. It has high air and moisture vapour permeability compared to its commercial counterpart and will provide satisfactory thermal comfort to the wearer in hot and humid environments. The overall thermal resistance performance, together with high flexibility and moisture management capability, make the aerogel-nonwoven fabric a potential alternative to commercial nonwovens for any thermal protective clothing system where fabric flexibility and thermal comfort are the key requirements.